Development of New Low-GWP Refrigerants–Refrigerant Mixtures Including HFO-1123. (3rd July 2019) - Hashimoto, Mai; Otsuka, Tetsuo; Fukushima, Masato; Okamoto, Hidekazu; Hayamizu, Hiroki; Ueno, Katsuya; Akasaka, Ryo
Abstract : New refrigerants with low global warming potential (GWP) are currently being developed to replace conventional higher GWP refrigerants. Recently, we have developed binary and ternary refrigerant mixtures, HFO-1123/HFC-32 and HFO-1123/HFC-32/HFO-1234yf. They showed azeotropic-like behavior and the potential to be an alternative to R-410A used in domestic and commercial air-conditioners. This work investigated the physical properties of these new refrigerants, including the critical parameters, PVT relation and compatibility with oils, and performed the theoretical cycle analysis. Equations of state developed from the physical properties were used in the theoretical analysis. The analysis showed that the performance of these new refrigerants are comparable to the performance of conventional ones. In addition, this work closely studied the self-decomposition of HFO-1123 and confirmed that it does not occur in the ordinary operating range of air-conditioning equipment.